Volume and energy folding landscape of prion protein revealed by pressure - Y. Cordeiro; J. Kraineva; R. Winter; J.L. Silva (Brazilian Journal of Medical and Biological Research, 2005)
The main hypothesis for prion diseases proposes that the cellular protein (PrP C) can be altered into a misfolded, ß-sheet-rich isoform, the PrP Sc (from scrapie). The formation of this abnormal isoform then triggers the transmissible spongiform encephalopathies. Here, we discuss the use of high pressure as a tool to investigate this structural transition and to populate possible intermediates in the folding/unfolding pathway of the prion protein. The latest findings on the application of high pressure to the cellular prion protein and to the scrapie PrP forms will be summarized in this review, which focuses on the energetic and volumetric properties of prion folding and conversion.